Non-isothermal pyrolytic kinetics of milk dust powder using thermogravimetric analysis. (December 2021) - Vikraman, V. Karuppasamy; Boopathi, G.; Kumar, D. Praveen; Mythili, R.; Subramanian, P.
Abstract: Milk dust is a prominent remnant of the milk powder packaging industry. The present study reports the thermal degradation pattern and pyrolytic kinetics of milk dust powder (MDP). Thermogravimetric studies were conducted at multiple heating rates (10, 20, 30, and 40 °C min −1 ) and the obtained biochars were characterized by FTIR, SEM, and XRD. Kinetic analysis was performed using model-free and model-fitting methods. The activation energy obtained by Starink and Friedman methods were 228.29 and 232.46 kJ mol −1, respectively. The frequency factor was found to be in the range between 2.69 × 10 10 and 4.37 × 10 32 s −1 as determined using the Kissinger method. The MDP pyrolysis followed diffusion (α = 0.05 to 0.2) ensued by higher-order (α = 0.6 to 0.95) reaction mechanism as predicted by the master plots. The change in enthalpy (144.88–405.42 kJ mol −1 ) and Gibb's free energy (176.98 and 182.21 kJ mol −1 ) implied the endothermic nature and non-spontaneity of MDP pyrolysis. Whereas ΔS values were negative in the conversion range (0.05–0.3) indicating that the process was spontaneous at initial conversions. The kinetic and thermodynamic analysis results confirm the suitability of milk dust powder as a potential candidate for energy conversion through pyrolysis. Graphical abstract: Image 1 Highlights: Pyrolysis kinetics of milk dust powder (MDP) is studied for the first time. Kinetic triplets were determined using model-free and model-fitting methods. Thermodynamic parameters revealed the potential of MDP as a pyrolysis feedstock.